Probate Inventories: A New Source for the Historical Study of Wealth, Material Culture and Agricultural Development : Papers Presented at the Leeuwenborch Conference (Wageningen, 5-7 May 1980) - Schuurman, Anton; Woude, Ad van der (HES Studia Historica, 1980)
Papers presented at the Leeuwenborch Conference (Wageningen, 5-7 may 1980).